Analisis Kritis Peran Ombudsman Republik Indonesia dalam Pengawasan Pelayanan Publik dan Implikasi Terhadap Akuntabilitas Publik: Kajian Literatur Perspektif Good Governance - Ria Aprian Hamadi; Vivi Oktari (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Public service oversight plays an important role in promoting the implementation of good governance principles, particularly in terms of transparency and accountability. However, in practice, there are still discrepancies between the concepts developed in the literature and the conditions found in the field. This study focuses on understanding these gaps by examining various theoretical studies and empirical findings related to the role of the Ombudsman of the Republic of Indonesia in public service oversight. This research employs a qualitative approach through a literature study, utilizing books, scientific journals, and legal documents as data sources. The data were analyzed using a descriptive-comparative method to identify relationships among patterns, research limitations, and several aspects related to the effectiveness of oversight. The findings indicate that, conceptually, the Ombudsman of the Republic of Indonesia functions as a supervisory institution that supports the realization of public accountability. However, in practice, this role has not yet been carried out optimally. Several factors contribute to this condition, including low public participation, limited authority in enforcing recommendations, and the absence of standardized indicators for measuring oversight effectiveness. These findings suggest that institutional strengthening, increased public participation, and the development of a more integrated oversight system are still needed to ensure that good governance principles can be realized more effectively and tangibly.